Pollen high-resolution record of Dansgaard-Oeschger variability in the Adriatic Sea (Central Mediterranean) - MASSAMBA N'SIALA, Isabella; MERCURI, Anna Maria; A. PIVA; F. TRINCARDI; R. R. SCHNEIDER (ALFRED-WEGENER-INSTITUT FUER POLAR- UND MEERESFORSCHUNG, COLUMBUSSTRASSE, 2008)
Long ice and marine cores reveal a more complete view of the range of climate variability and associated biotic responses, allowing the monitoring of long term trends in the character of this variability. Oxygen isotope records from Greenland ice cores indicate numerous rapid climate fluctuations during the last glacial period: there was first defined the record of high frequency Daansgard-Oeschger climate variability. More recently, evidence of these short-term oscillations was found also in the Western Mediterranean (Alboran Sea and Gulf of Lions) marine records. The multi-proxy study of very expanded successions of marine sediments within EC-EUROSTRATAFORM project allows, for the first time in the Adriatic basin the recognition of high frequency oscillations during the last 70 ka. The semi-enclosed, land-locked nature of the Adriatic Sea plays a key role in amplifying the intensity of the climate variations, making them evident in different cores. The paleoenvironmental meaning of these Adriatic oscillations is particularly significant, considering the important role of this basin in ventilating the eastern Mediterranean through the production of dense water masses. The pollen evidence of these high resolution climate variability records found good results mainly in continental lacustrine contests. This study presents a pollen dataset reflecting the climate changes in Central Mediterranean marine records, placing emphasis on the moisture and temperature variation effects on the pollen represented vegetation. In the studied cores, Artemisia is one of the most representative taxa to monitor the cold and dry oscillations during the last glaciation. The study of Daansgard-Oeschger cyclicity in Adriatic cores located in different water depths is investigated with an integrated approach: as pollen, other independent proxies are studied and correlated, like planktic and benthic foraminifera and oxygen stable isotopes; moreover, the chronology is constrained by several 14C AMS dates and by tephro-stratigraphic and ...